(untitled) (Actualité en allergologie et en immunologie au Canada, 2025)
The European Academy of Allergy and Clinical Immunology (EAACI) Congress 2025, held in Glasgow, Scotland, United Kingdom from June 13 to 16, centred on the overarching theme of “Breaking boundaries in Allergy, Asthma, and Clinical Immunology: Integrating Planetary Health for a Sustainable Future.” Indeed, this year’s theme emphasized the intersection of environmental health and allergic diseases. The vibrant congress featured several presentations on immunological diseases in both adult and pediatric populations, along with breakthroughs in clinical and translational domains. Key topics included asthma, allergy, chronic spontaneous urticaria, and current global challenges such as pollution and climate change. This report highlights several key studies, organized under three main themes: pediatric studies, biologics in combined airways disease, and biomarkers.